SUPERVISI KLINIS-GROW ME SEBAGAI MODEL SUPERVISI YANG EFEKTIF DI SMA N 1 JASINGA KABUPATEN BOGOR - Agus Sarifudin (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Research of school action (Penelitian Tindakan Sekolah) has used at one of school in West Bogor. The goal are to know klinis supervision benefit at school, to hold professional learning community and to get effective klinis supervision. The result of learning problem identification are media (15%), material ( 6%), student (45%), teaching material (19%) and method (15%). There are two period of Grow Me Klinis Supervision at school MGMP. The factors observed are teacher activity, teacher learning, and student attitude. The result of research second periode is better than first period. Teacher activity at the first periode is 54,94%, at second period is 78,69%, so at second period is better than first period 23,75%. Learning process implementation at first period is14,58%, at second period is 36,12%, so the second is better than the first 21,54%. The result of research second period Grow Me Klinis Supervision can improve learning quality and quantity, and learning implementation. There can improve activity, attitude, interest teacher and student. Grow Me Klinis Supervision more effective than ordinary klinis supervision.Â Kata kunci: Grow Me, supervisi klinis